CLINICAL AND LABORATORY PARAMETERS AND THEIR RELATIONSHIP WITH THE LEVEL OF MAGNESIUM IN OSTEOARTHRITIS AGAINST THE BACKGROUND OF UNDIFFERENTIATED CONNECTIVE TISSUE DYSPLASIA - Akhmedzhanova Diyora Marufovna (Modern American Journals, 2025)
The purpose of this work is to conduct a comparative analysis of the parameters of antibodies to type I collagen and their relationship with Mg2+ ions in patients with osteoarthritis against the background of undifferentiated connective tissue dysplasia (UCTD). The study involved 88 individuals aged 25 to 55 (35.2±1.89) years with phenotypic signs of UCTD and osteoarthritis. In patients with osteoarthritis against the background of UCTD, there was a decrease in the level of Mg2+ ions and an increase in titers of autoantibodies to type I collagen. The dynamics of changes in the level of autoantibodies, as well as magnesium, depending on the severity of the clinical course of osteoarthritis against the background of UCTD, can serve as a method for assessing the progression of the pathological process and prognosis of the disease.
Keywords: Osteoarthritis, undifferentiated connective tissue dysplasia, magnesium ions (Mg2+), autoantibodies to type I collagen.